FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT KEPATUHAN PERUSAHAAN GO PUBLIC PADA KONVERGENSI INTERNATIONAL FINANCIAL REPORTING STANDARD (Studi Empiris pada Perusahaan yang Terdaftar di Index LQ45) - Aldo Ganesha; Endang Kiswara (Diponegoro Journal of Accounting, 2015)
This study aimed to examine the effect of firm size, profitability, leverage, auditor type, listing status, international visibility, and the types of companies on the level of compliance of the public company  with  IFRS  convergence  in  2012.  This  research  was  conducted  by  method  of documentation on the financial statements on listed in the index LQ45 Indonesia Stock Exchange (IDX) and analyzed using multiple linear regression model. The results of this study showed that only type of auditor has significant positive effect on the level of compliance of the public company on IFRS convergance in 2012. This is due to the company in Indonesia which financial statements will be audited by the big four, tend to have used PSAKs converging with IFRS. This is what makes the auditor type variable has a positive and significant effect on the level of compliance with IFRS in Indonesia.